Revision of the genus Callaspidia Dahlbom, 1842 (Hym.: Figitidae: Aspicerinae) - Ros-Farré, P.; Pujade-Villar, J. (Zootaxa, 2009)
Callaspidia Dahlbom is an Aspicerinae genus (Hymenoptera: Cynipoidea: Figitidae) with a Holartic distribution. One species, Callaspidia defonscolombei Dahlbom is cited from South America; however, it has probably been introduced. The morphological features needed to differentiate species of Callaspidia are described. Species in this genus possess much intraspecific variability compared with other morphologically homogeneous Aspicerinae genera. Callaspidia originally included 19 species and two subspecies prior to this study. The type material of 16 species of Callaspidia has been studied, but type material from Callaspidia areolata (Kieffer, 1901), C. dichroa Belezin, 1927, C. dufouri spp vitripennis (Kieffer, 1901), C. dusmeti Tavares, 1924, C. fonscolombei spp minima (Kieffer, 1901), C. marshalli (Kieffer, 1901), C. mediterranea Dalla Torre & Kieffer, 1910, and C. rubricrus Dettmer, 1924, is lost or has been destroyed. Out of these 16 studied species, only five are considered valid and are redescribed here. The examination of hundreds of additional specimens supplied by different institutions suggests that there is a general lack of knowledge concerning the intraspecific diversity. A new species is described: Callaspidia dahlbomi Ros-Farré & Pujade-Villar n. sp. A key to the six valid species of Callaspidia is given. All species are illustrated. The status of Figites latreilli Hartig, 1840 is discussed, resulting in Omalaspis latreilli (Hartig) n. comb.